Pace and Sequencing of Economic Policies - Zalduendo, Juan (IMF Working Papers; Working Paper ;, 2005)
This paper examines the design of economic policies using factor analysis, which has several advantages; in particular, it limits the problems that typically arise from the high correlation of economic policy indicators, it helps in identifying clusters of economic policy, and it facilitates the derivation of policy design indicators that represent the pace and sequence of economic policies. Econometric results show that the introduction of sound economic policies has both level effects and growth effects, suggesting it is necessary to exercise caution when assessing a country's growth prospects immediately following the introduction of new policies. In addition, the results suggest that growth strengthens when a country implements policies that outpace either a notional measure of "world average policies" or a country's own policy trend, and highlight the critical role played by macroeconomic vis-a-vis microeconomic policies. The latter also reveals the existence of sequencing factors in policy implementation; for example, trade liberalization and financial liberalization positively affect growth, but more so if economic stability and fiscal sustainability have been secured.